The efficiency of Malaysian Islamic banks: Intermediation, production and operating approach - Chowdhury, Mohammad Abdul Matin; Haron, Razali (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
The Malaysian Islamic banking industry holds one of the top three market shares for global Islamic banking assets. Apparently, a dual banking system involving conventional and full-fledged Islamic banks are currently operating in Malaysia. The main objective of this study is to evaluate and compare the efficiency of conventional-owned Islamic banks and full-fledged Islamic banks using three banking approaches. To achieve this objective, information from the annual reports of 15 Islamic banks were utilised from 2011 to 2018. The findings provided mixed evidence subject to the different approaches of DEA methodology. Full-fledged Islamic banks outperformed conventional-owned Islamic banks in the intermediation approach, while conventional-owned Islamic banks outperformed in the production and operating approaches. The findings provide inputs for banks to increase their competency at the managerial level and for policymakers to sustain the growth momentum of the industry.